A novel solution for preventing leading edge erosion in wind turbine blades. Issue 3 (3rd July 2021) - Finnegan, William; Flanagan, Michael; Ó Coistealbha, Rónán; Dasan Keeryadath, Priya; Meier, Patrick; Chi Hung, Le; Flanagan, Tomas; Goggins, Jamie
ABSTRACT: Over the past 30 years, wind energy has been established as one of the leading forms of renewable energy. As the industry grows so too does the size of the wind turbines themselves – large wind turbines can now generate up to 15 MW. However, with larger turbines comes additional structural challenges to overcome, where one such challenge is erosion along the leading edge of the blade due to water impingement at the higher tip speeds of the blade. Therefore, in this paper, the development of a novel solution for preventing leading edge erosion on wind turbine blades (LEP) is presented. Primarily, this paper describes the experimental testing campaigns that were performed during LEP development. Based on the results from the rain erosion testing of selected materials, their manufacturability and other mechanical properties, thermoplastic polyurethane has been selected as the most suitable material to manufacture the LEP. The LEP component was de-risked through demonstrator testing and then bonded to the leading edge of a full-scale wind turbine blade. Structural (dynamic, static and fatigue mechanical) testing was performed on the blade with no significant damage observed. The next stage of development is operational trials on a wind turbine in marine conditions.